2013
DOI: 10.1111/1471-0528.12242
|View full text |Cite
|
Sign up to set email alerts
|

Unsafe abortion after legalisation in Nepal: a cross‐sectional study of women presenting to hospitals

Abstract: Objective To investigate abortion practices of Nepali women requiring postabortion care.Design Cross-sectional study.Setting Four tertiary-care hospitals in urban and rural Nepal.Sample A total of 527 women presenting with complications from induced abortion in 2010.Methods Women completed questionnaires on their awareness of the legal status of abortion and their abortion-seeking experiences. The method of induction and whether the abortion was obtained from an uncertified source was documented. Multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 17 publications
6
55
1
Order By: Relevance
“…It is a safe, cheap, long-acting, reversible, and non-hormonal contraceptive method that is highly effective for prevention of unwanted pregnancies and the abortion-related complications [1][2][3][4][5]. PPIUD can promote the health of mothers and children by preventing financial, psychological, obstetric, and other health complications associated with short-interval pregnancies [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is a safe, cheap, long-acting, reversible, and non-hormonal contraceptive method that is highly effective for prevention of unwanted pregnancies and the abortion-related complications [1][2][3][4][5]. PPIUD can promote the health of mothers and children by preventing financial, psychological, obstetric, and other health complications associated with short-interval pregnancies [2].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests there are missed opportunities to provide information and counselling on family planning methods and services to postpartum women. Studies conducted in Nepal have shown that unintended pregnancies, due to low use of contraception and reliance on less effective family planning methods (traditional methods), have caused repeated abortions and abortion-related complications [9, 10]. Therefore, to consolidate and extend the achievements made in maternal and child health, increased access to quality family planning services and strengthened postpartum counselling will be instrumental.…”
Section: Introductionmentioning
confidence: 99%
“…Face to face interview 36-41,44 and application of a self-administered questionnaire 31-33,35,43 in queries about illegal abortion were the most common reported data collection method respectively. The study’s findings have also revealed that married 25-27,31,33,35,38,39,41,43 and unemployed women 25-27,29,35,37,38,40,43,44 of 26-30 years old age group 35-38,41,42 with 1-2 children 9,13,16,19,25,31,34,35,37,41,43 and low socioeconomic backgrounds 7,13,16,17,21,27,38,39,40,42 were the most typical illegal abortion seekers in the included studies. The observed partial inconsistency in the attributes of the abortees in the quoted studies; however, may reflect inherent cultural differences regarding pre-marital sexual relationship, out of wedding pregnancies or aberrant methodologies used.…”
Section: Discussionmentioning
confidence: 99%